VD_FINDINFO AP / 2010 / 53 vom 26. November 2009 - VD Tribunal cantonal (2009)
VIOLATION DE L'OBLIGATION DE TENIR UNE COMPTABILITÉ, GESTION FAUTIVE | 165 ch. 1 CP, 166 CP, 34 ch. 2 CP, 411 let. h CPP, 411 let. i CPP, 415 CPP, 439 al. 1 CPP